Strong downslope winds and application of hydraulic-like theory - Helmis, C.G.a b; Flocas, H.A.a b; Kalogiros, J.A.a b; Asimakopoulos, D.N.a b (Journal of Geophysical Research D: Atmospheres, 2000)
An experimental campaign was conducted at the lee side of a 1 km high steep mountain in order to study the development of strong downslope winds under favorable conditions, using combined remote and insitu instrumentation. The examination of the upstream atmospheric conditions reveals that the development of strong downslope winds is favored by a mean state critical layer or a significant decrease in static stability (such as at the top of a temperature inversion) at the proper height above the mountain top. Strong downslope winds could occur even for wind directions with a deviation of 60° off the axis perpendicular to the ridgeline, as long as the cross-mountain wind has a significant value (at least 7 ms-1). The developed disturbances are associated with intense downdrafts of the order of 4-5 ms-1 within the first 600 m above ground and characteristic vertical turbulent structures that were observed by sodar. The same phenomenon is observed not only during nighttime but also under unstable and neutral conditions of the atmospheric boundary layer (ABL) albeit with weaker intensity. Fourier analysis of the vertical velocity field demonstrated that the typical time period of intense disturbances was about 5 min. Further evidence is also provided for the application of the hydraulic-like theory under real atmospheric conditions. Copyright 2000 by the American Geophysical Union.
Keywords: mountain; topographic effect; wind